دراسة الخرع الناجم عن عوز الفيتامين (د) عند الأطفال - حكيم مأمون; ديوب عدنان; الطواشي رفاه (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة على 42 مريضا يبدون تظاهرات سريرية للخرع العوزي إضافة إلى 42 طفلا آخر كمجموعة شاهد، وكان متوسط أعمار مجموعتي الدراسة 20 شهرا . وجدنا أن معظم المرضى يعيشون في منازل غير مشمسة في المدينة و نشؤوا في كنف أمهات ذوات مستوى ثقافي متدن و كانوا ذوي جلد داكن اللون. كانت تغذية غالبية المرضى في السنة الأولى من العمر تعتمد على الإرضاع الوالدي من أمهات ذوات جلد داكن اللون ولم يتعرضن بشكل كاف لأشعة الشمس كما تبين أيضا أن حليب البقريشكل عاملا مؤهبا هاما للإصابة الخرعية. وقد وجدنا أيضا أنه على الرغم من كون ضخامة المشاش في المعصمين و الكاحلين علامة هامة للخرع إلا أن التابس القحفي كان أبكر هذه العلامات ظهورا. لدى جميع المرضى حدث ارتفاع في المستوى المصلي للفوسفاتاز القلوية وذلك بشكل متناسب مع شدة الإصابة الشعاعية المقاسة. لقد شكل فشل النمو اختلاطا هاما للخرع العوزي بينما كان التكزز الخرعي و هو الاختلاط الخطير المهدد للحياة غير شائع(حدث بنسبة4.8%). من خلال الدراسة و جد أن الإنتانات التنفسية المتكررة و فقر الدم بعوز الحديد هي أمراض شائعة مرافقة للخرع العوزي (حدثت بنسبة 30.9% للأولى و 28.6% للثانية عندا لمرضى ) This study was carried out on 42 patients demonstrating clinical features of vitamin _D_ deficiency rickets, and on other 42 children as a control group. The mean age of the study groups was 20 months. We found out that most patients lived in houses with insufficient sunlight in the city, reared by mothers of low educational attitudes, and were dark-skined. The vast majority of patients were breast-fed by dark-skined mothers who did not have enough exposure to sunlight, and we discovered that cow milk was an important predisposing agent to rickets, we also found out that although epiphysed enlargement of the wrists and the ankles was the most common sign, craniotabes was the earliest one. Alkaline phosphatase was elevated in all patients in proportion to the radiographic scoring Growth failure was a common complication of rickets but patients weight was appropriate to height in all, rachitic tetany the life-threating complication was uncommon (the rate 4,8%). Recurrent respiratory tract infections and iron-deficiency anemia were common as rickets-associated diseases at a rate 30,9%for the former,and28,6%for the latter.